A somposition-based approach to the description of the solid-solution hardening in binary solutions with unrestricted solubility of components - Firstov, S.A.; Rogul, T.G. (Reports of the National Academy of Sciences of Ukraine, 2018)
A new approach based on the assumption of a composition-cluster structure to the description of the hardening in binary solid solutions with unrestricted solubility of components is considered. An expression is proposed for the concentration dependence of the critical shear stress in unbounded solids, in which the hardening with increasing the concentration of a doping component is proportional to the value of c (1 − c).